Metaverse Marketing: New Opportunities for Creative Entrepreneurs in Building Consumer Experience - Aditi, Bunga; Prasetya, Victor; Hafas, Hafriz Rifki (Jurnal Informatika Ekonomi Bisnis, 2025)
The emergence of the metaverse has transformed digital marketing by offering immersive and interactive experiences that reshape consumer behavior. This study explores the role of metaverse marketing as a new opportunity for creative entrepreneurs in building consumer experience and behavioral intention. Using a quantitative approach, data were collected from 282 respondents who had interacted with creative entrepreneurship activities in the metaverse, such as virtual fashion shows, digital music concerts, and art exhibitions. The measurement model was validated for reliability and validity, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that immersiveness, sociability, and environmental fidelity significantly affect consumer experience, which in turn strongly influences purchase intention and loyalty. Moreover, consumer experience partially mediates the relationship between metaverse characteristics and behavioral intention. These findings highlight that creative entrepreneurs should focus not only on adopting new technologies but also on designing valuable and meaningful experiences for their consumers. This study contributes to the literature on digital marketing and entrepreneurship by emphasizing the strategic role of the metaverse in fostering sustainable consumer engagement.